Uncommon cause of acute appendiceal torsion mucocele. Issue 7 (4th July 2022) - Nyandoro, Munyaradzi Gift; Palanisamy, Vignesh Kumar; Singh, Rajesh Kumar
Abstract : Appendiceal torsion is a rare phenomenon, presenting with symptoms mimicking acute appendicitis. Preoperative imaging generally has a low pick-up rate of appendicular torsion and is thus mostly diagnosed intraoperatively. The cause of the appendicular torsion should guide the required surgical resection to ensure adequate oncological treatment. Therefore, emphasis should be placed on minimal tissue handling in such operative cases to reduce the risk of accidental rupture, tumour spillage and spread.